Estimating the Cost of Mining Pollution on Water Resources: Parametric and Nonparametric Resources - Herrera Catalán, Pedro (2012)
This study estimates the economic costs of mining pollution on water resources for the years 2008 and 2009 based on the conceptual framework of Environmental Efficiency. This framework identifies such costs as the mining companies’ trade-off between increasing production that is saleable at market prices (desirable output) and reducing the environmental pollution that emerges from the production process (undesirable output). These economic costs were calculated from parametric and non parametric production possibility frontiers for 28 and 37 mining units in 2008 and 2009, respectively, which were under the purview of the National Campaign for Environmental Monitoring of Effluent and Water Resources, conducted by the Energy and Mining Investment Supervisory Agency (Osinergmin) in those years. The results show that the economic cost of mining pollution on water resources rose to U.S. $ 814.7 million and U.S. $ 448.8 million for 2008 and 2009, respectively. These economic costs were highly concentrated in a few mining units, within a few pollution parameters, and were also higher in mining units with average/low mineral production. Taking into consideration that at present the fine and penalty system in the mining sector is based on administrative criteria, this study proposes a System of Environmentally Efficient Sanctions based on economic criteria so as to establish a preventive mechanism for pollution. It is hoped that this mechanism will generate the necessary incentives for mining companies to address the negative externalities that emerge from their production process.